The Use of the “Word Wall” Strategy to Improve Vocabulary Mastery in English Learning - As Rakib, Andi Maharani; Noni, Nurdin; Samtidar, Samtidar (PERFORMANCE: JOURNAL OF ENGLISH EDUCATION AND LITERATURE, 2024)
This research aims to find out whether there is an improvement in the vocabulary mastery of students of SMPN 40 Makassar by using the "Word Wall" strategy. This research used pre-experiment research. This research was conducted in one group only and there was no comparison group, namely by using a one-group pre-test post-test design. The population of this research consists of all eighth-grade students’ at SMPN 40 Makassar in the 2023/2024 academic year. The sample of this research is was 29 students of class VIII-D at SMPN 40 Makassar. The instrument of this research is testing, namely pre-test and post-test. The result of this research is that the significance value for the learning outcome variable is 0.000 which means it is lower than the significance degree <0.05. So, it can be concluded that there is a significant improvement in the mastery of English vocabulary of SMP 40 Makassar students by using the "Word Wall" strategy.Keywords: Vocabulary Mastery, “Word Wall” Strategy